Three Poems - Wolfe, Kathi (Disability Studies Quarterly, 2008)
Kathi Wolfe is a poet and writer. She was a finalist in the 2007 Pudding House Press Chapbook Competition. Her chapbook Helen Takes the Stage: The Helen Keller Poems was published in 2008 by Pudding House Press. Wolfe's poetry has appeared in Wordgathering , Breath & Shadow , Gargoyle , Potomac Review , Beltway Poetry Quarterly and other publications. She has read at the Library of Congress Poetry at Noon Series and appeared on the public radio show "The Poet and the Poem."